1999
DOI: 10.1021/bi9823232
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Saturation Magnetization Properties of the Manganese- and Cobalt-Substituted Fur (Ferric Uptake Regulation) Protein from Escherichia coli

Abstract: The Fur apoprotein has been purified and reconstituted with Co2+ and Mn2+ ions. These samples have been analyzed by UV-visible, EPR, and 1H NMR spectroscopies, by XAS, and by magnetization measurements. The apo-Fur protein is able to bind one metal dication (Co2+ or Mn2+) per monomer. A saturation magnetization study confirms the presence of a high-spin metal dication [Mn(II) S = 5/2 and Co(II) S = 3/2]. The two metal ions per Fur dimer are not in magnetic interaction (|J| < 0.1 cm-1 ). The UV-visible spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 67 publications
8
75
1
Order By: Relevance
“…Recent data concerning the nature of the ligands coordinated to iron in FeFur are much more in agreement with the environments in these compounds. Indeed, spectroscopic data on cobalt-and iron-substituted Fur indicated that the metal is hexacoordinated with one ligand at a longer distance and only nitrogen and oxygen donor ligands including two (or three) histidines and one (or two) aspartate or glutamate (20,21). In conclusion, the nature of the EPR signal of the nitrosyl iron species in the FeFur-NO complex cannot be assigned without further spectroscopic characterizations.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Recent data concerning the nature of the ligands coordinated to iron in FeFur are much more in agreement with the environments in these compounds. Indeed, spectroscopic data on cobalt-and iron-substituted Fur indicated that the metal is hexacoordinated with one ligand at a longer distance and only nitrogen and oxygen donor ligands including two (or three) histidines and one (or two) aspartate or glutamate (20,21). In conclusion, the nature of the EPR signal of the nitrosyl iron species in the FeFur-NO complex cannot be assigned without further spectroscopic characterizations.…”
Section: Discussionmentioning
confidence: 92%
“…Fur expression was induced at OD 600 ϭ 0.7-0.8 by isopropyl ␤-D-thiogalactoside (200 mM, 600 l) during 2 h and 30 min. Dimeric Fur protein was purified as described (20). The buffer was exchanged for 100 mM 1,3-bis[tris(hydroxymethyl)methylamino]propane͞100 mM KCl, pH 7.5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectroscopic characterization of these systems has revealed that cobalt can be present as Co(II) and Co(III) ions in several types of coordination, which lead to different electronic and magnetic properties. In this context, the use of simple Cocontaining systems with low molecular weight ligands is useful for understanding the correlation between spectroscopic and structural properties [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%